岐阜県熊石洞産の後期更新世のヒグマ，トラ，ナウマンゾウ，カズサジカ，カモシカ属の化石 - 樽野, 博幸; 3640; タルノ, ヒロユキ; 石田, 克; 1074; イシダ, シノグ; 奥村, 潔; 1073; オクムラ, キヨシ; Taruno, Hiroyuki; 3644; ISHIDA, Shinogu; et al. (大阪市立自然史博物館, 2018)
熊石洞は日本の代表的な後期更新世の哺乳類化石産地の一つで，29種が知られている.本稿 ではこれらの中で，ヒグマ Ursus arctos，トラ Panthera tigris，ナウマンゾウ Palaeoloxodon naumanni， カズサジカCervus(Nipponicervus)kazusensis，ニホンカモシカ近似種Capricornis sp., cf. C. crispusの 記載を行った.トラとカモシカ属の化石は，熊石洞からは初めての報告である.その中で，以下の 点について議論し見解を明らかにした.1ヒグマUrsus arctosとツキノワグマU. thibetanusとの上顎 第4小臼歯における識別点，2ナウマンゾウ Palaeoloxodon naumanni の第3・第4乳臼歯と第1大臼歯の 咬板数，3中型シカ類ではカズサジカ Cervus(Nipponicervus)kazusensis のみが産出し，ニホンジカ Cervus(Sika)nipponの産出は確認できない，4ニキチンカモシカNaemorhedus nikitiniはゴーラル属 Naemorhedus ではなくカモシカ属 Capricornis に属する，5日本の更新世のカモシカ属は，現生のニ ホンカモシカより大型である. Kumaishi-do Cave is one of representative Late Pleistocene mammalian fossil localities in Japan. The excavations of fossiliferous sediments in the cave had produced 29 mammalian species. This paper provides detailed systematic descriptions for the remains of Ursus arctos, Panthera tigris, Palaeoloxodon naumanni, Cervus(Nipponicervus)kazusensis and Capricornis sp. cf., C. crispus. Among them, Panthera tigris and the genus Capricornis are described as the first records from Kumaishi-do Cave. This paper contains discussions as follows:(1)Features of the upper fourth premolars, which distinguish Ursus arctos from U. thibetanus;(2)the number of the lamellae of the third and fourth milk molars and the first molar of Palaeoloxodon naumanni;(3)among the middle-sized cervids, only the remains of Cervus(Nipponicervus) kazusensis have been discovered, and no Cervus(Sika)nippon remains known from the Kumaishi-do Cave; (4)Naemorhedus nikitini is possibly transferred to the genus Capricornis;(5)the Pleistocene form of Japanese serow(Capricornis)was larger than extant Capricornis crispus. departmental bulletin paper